ID 287 – Sensory feedback generated by intraneural electrical stimulation of peripheral nerves drives cortical reorganization and relieves phantom limb pain: A case study. Issue 3 (March 2016) - Granata, G.; Vecchio, F.; Miraglia, F.; Raspopovic, S.; Petrini, F.; Micera, S.; Rossini, P.M.
Abstract : Phantom limb pain (PLP) is a frequent consequence of amputation and the challenge remains to find a long-lasting treatment. Recent evidence suggests that PLP is likely correlated to aberrant plastic changes in the cortex. We aimed to counteract these changes through sensory feedback generated by intraneural electrical stimulation and thereby control and alleviate pain. A 34-year-old male with a left hand/forearm amputation had four intraneural electrode arrays implanted in the median and ulnar nerves for 30 days. We developed and tested a prototype system to drive sensory feedback through intraneural electrical stimulation. Functional testing was first carried out to map the type, strength, and location of the sensations generated by electrical stimulation. We then selected specific stimulation sequences that were applied in repeated sessions. The pain perception and cortical neurophysiological maps were measured before and after these sessions. The participant experienced a decrease in the pain perception (rated from 8 to 4–5 at VAS) during and up to a few hours after the stimulation sessions. We also found a change in the somatosensory map of the right cortical hemisphere. Intraneural electrical stimulation was able to reliably generate sensory feedback, modulate cortical organization, and temporarily relieve PLP.